Pengaruh Inovasi, Budaya Organisasi dan Teamwork Terhadap Kinerja Manajerial Serta Implikasinya Pada Kinerja Bank Perkreditan Rakyat di Provinsi Kalimantan Timur - Rediyono, * (Program Doktor Ilmu Ekonomi, 2013)
Bank Performance were very depend on human resource. In high competition, organization behaviour should be managed to match with internal and external condition. In this context, bank need corporate culture which support effective teamwork and create innovation by hold of management. Management who responsible to manage organization should have competency to transforming opportunities to realize the vision. So, managerial performance have great impact on corporate performance. Many research of corporate performance use single methode to evaluate a performance so it is difficult for us to get a comprehensive profile. The objective of this disertation are to analyse the effects of innovation, corporate culture, teamwork on managerial performance on corporate perfor-mance of commmunity banking in Province of East Kalimantan. The different of this research compare with others, is using Balanced Scorecard model to evaluate corporate performance to get a comprehensive profile and Team work as one of Predicting variable. Total 140 respondents from 14 community banking in Province of East Kalimantan partici-pated in this study. The data were collected using questionnaires and analyzed using Structural Equation Modelling (SEM).Results of this study proved that innovation, corporate culture and teamwork have significant effects on managerial performance. Managerial performance and teamwork also have significant effects on corporate perfor-mance. On the contrary, innovation and corporate culture have insignificant effects on corporate performance inÂ commmunity banking in Province of East Kalimantan.Â The finding of this study is important empirical evidence on the development of organi-zation behaviour theories and practices.Key words: community banking, innovation, corporate culture, teamwork, managerial, and performance.